PHILOSOPHICAL-FUTUROLOGICAL THOUGHTS OF ACADEMICIAN O.A. TOGUSAKOV (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article is an academic study that combines philosophy and futurology to understand contemporary changes in society. The article discusses the idea of academician O.A. Togusakov that these changes require new philosophical thinking and a futurological approach to understand and adapt to them. Academician O.A. Togusakov offers various concepts and hypotheses that help to understand the essence of these changes and their potential consequences. It calls for philosophical reflection and dialogue to find ethical guidance and guidance in the face of rapid technological development and social change. In general, the article represents the academician’s contribution to the development of philosophy and futurology as disciplines that can help a person adapt to the transformations of society.
Keywords: academician, hypothesis, concept, cultural studies, political science, rights, sociology, philosophy, futurology.